A Tool to Guide Creation of Products for Risk Communications and Community Engagement (RCCE) - Tam, Wai Jia; Gobat, Nina; Hemavathi, Divya; Fisher, Dale (Frontiers in Public Health, 2022)
Using best practices to produce creative, relatable, contextualized health messaging contributes to effective risk communication. During emergency disasters, the landscape of mis- and dis-information demands strategic, collaborative approaches across all stakeholders particularly government and the media to ensure effective public messaging. However, tools for new RCCE practitioners and media agencies such as television producers and advertising firms to rapidly create effective RCCE products are currently not readily available. In response to concerns that vaccine hesitancy may become more evident once a significant proportion of the population had been reached, the Ministry of Communications and Information (MCI) in Singapore launched a public health music video on 2 May 2021, making headlines globally and garnering more than 5 million views worldwide. The video aimed to dispel myths and concerns about vaccinations and encouraged citizens to get their vaccination quickly rather than wait. We aimed to evaluate this video as a case study and articulate why it is an example of good practice in risk communications. Working inductively to identify emergent principles of product creation in this case study and analyzing them against existing RCCE frameworks and recommendations helped develop a practical tool to guide the rapid creation of RCCE products by those who may be unfamiliar to RCCE principles. This tool can help new RCCE practitioners and media agencies to produce effective products in times of crisis. The easy-to-use tool provides a brief checklist that guides rapid creation of RCCE products, including criteria for understanding the target audience, message comprehension, development, reach and impact measurement. Given its derivation from existing RCCE frameworks and health literacy concepts, these can potentially be applied across different modalities and diverse cultures. Future work would include validation of these criteria and evaluation of its utility to strengthen RCCE as core in an emergency response.